Covid-19, Trust, And Vulnerability In North Halmahera District of Indonesia - Yerik Afrianto Singgalen (ARISTO, 2021)
Trust is an aspect that is very vulnerable to changes in the element of social capital. The loss of trust impacts the networks and norms accumulated to maintain forms of social capital. During the Covid-19 pandemic, the government limiting individuals' distance through the jargon of "physical distancing" or "social distancing." On the other hand, as a supporting aspect of trust, honesty plays an essential role in tracking interactions between individuals exposed to Covid-19. In the context of the society in North Halmahera, strengthening social capital is supported by cultural aspects. However, during the Covid-19 pandemic, trust levels degraded, weakening the previously accumulated cultural-based social norms and networks. This study used a qualitative method with a case study approach in North Halmahera District to identify social capital vulnerability during the Covid-19 pandemic. Local communities, as farmers, fishers, and small traders, were involved as key informants. This study indicates a transformation of the social capital structure that substantially changes cultural-based social capital's fundamental values into information-based social capital values. The social capital structure transformation was stimulated by the Large-Scale Social Restrictions (PSBB) policy, which increased social media use intensity. In Addition, trust was an aspect of vulnerability in the social capital structure during the Covid-19 Pandemic.